Proceedings of the Seventh International Conference on Information and Communication Technologies and Development 2015
DOI: 10.1145/2737856.2737878
|View full text |Cite
|
Sign up to set email alerts
|

Participatory video for nutrition training for farmers in Malawi

Abstract: This paper explores how participatory video can improve the knowledge and adoption of nutrition and food preparation practices among smallholder farmers in Malawi. Using a pretestposttest quasi-experimental design, this study found that the participatory video method improved the participants' knowledge as much as the traditional demonstration method. Short-term adoption tests were carried out 7-10 days after the training. The extent of short-term adoption of the technique varied by the training topic. For egg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…The concept of critical nutrition literacy is associated with cognitive and social skills to: 1 ) think critically about the merit and application of nutrition information and to implement change in personal nutrition behavior and lifestyle, and 2 ) to exercise one's agency to address obstacles to behavior change through increased engagement in social action ( 8 ). Our results are consistent with research highlighting the influence of PV on participants’ personal behavior – the first component of critical nutrition literacy ( 16 , 17 , 18 , 19 , 20 , 21 ). There are no published studies on the influence of a PV nutrition intervention on participants’ engagement in social action – the second component of critical nutrition literacy.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The concept of critical nutrition literacy is associated with cognitive and social skills to: 1 ) think critically about the merit and application of nutrition information and to implement change in personal nutrition behavior and lifestyle, and 2 ) to exercise one's agency to address obstacles to behavior change through increased engagement in social action ( 8 ). Our results are consistent with research highlighting the influence of PV on participants’ personal behavior – the first component of critical nutrition literacy ( 16 , 17 , 18 , 19 , 20 , 21 ). There are no published studies on the influence of a PV nutrition intervention on participants’ engagement in social action – the second component of critical nutrition literacy.…”
Section: Discussionsupporting
confidence: 91%
“…The results of 2 studies showed the important role of participatory activities in amplifying the influence of PVs. Cai et al ( 19 ) looked at the influence of locally made nutrition videos on audience members’ knowledge and behavior in comparison to a more participatory live food demonstration. Their results showed that although watching a PV increased knowledge, it did not improve change in nutrition behavior as much as live demonstrations ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation